Sushi or Fish Fingers? Seafood Diversity, Collapsing Fish Stocks, and Multispecies Fishery Management*. (10th April 2013) - Quaas, Martin F.; Requate, Till
Abstract We present a model of a multispecies fishery, and we show the following. (i) Consumer preferences for seafood diversity can trigger a sequential collapse of fish stocks under open‐access fishery. (ii) The stronger the preferences are for diversity, the higher is the need for coordinated multispecies regulation. (iii) Second‐best optimal management of only one (or a few) species is less strict than socially optimal management of the same species. (iv) Myopic regulation of one species, ignoring spillovers to other species, can cause depletion of other stocks that would not be depleted under open access.